2011
DOI: 10.1111/j.1750-3841.2011.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Volatile Compounds of Peanut Oil during the Roasting Process for Production of Aromatic Roasted Peanut Oil

Abstract: ARPO is the traditional edible oil in China that possesses a characteristic strong nutty and roasty flavor that distinguishes it from other edible vegetable oils. During the production, the roasting process is the crucial factor for the formation of the typical roasted peanut aroma that plays an important role in sensory quality of peanut oil. In our investigation, not only the volatile changes of peanut oil pressed from relevant peanut seeds roasted at different roasting time were determined, but also the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 32 publications
13
126
0
Order By: Relevance
“…These results may justify the similarity in their performance in this test compared to other test oils. These results may be supported by the results reported earlier that said GNO is analogous to SO [14]. However, GNO and SO reflected the highest records in viscosity (0.0574 and 0.0562 Pa. S -1 at 26 ° C, respectively) and the corresponding results at 38 ° C were (0.0380 and 0.0351 Pa. S -1 ) (table 4).…”
Section: Resultssupporting
confidence: 81%
“…These results may justify the similarity in their performance in this test compared to other test oils. These results may be supported by the results reported earlier that said GNO is analogous to SO [14]. However, GNO and SO reflected the highest records in viscosity (0.0574 and 0.0562 Pa. S -1 at 26 ° C, respectively) and the corresponding results at 38 ° C were (0.0380 and 0.0351 Pa. S -1 ) (table 4).…”
Section: Resultssupporting
confidence: 81%
“…Each of these components has been previously detected in experiments analyzing the volatile headspace of peanut samples (Chetschik et al, 2010; Liu et al, 2011; Ng et al, 2008). However, because these and other studies have identified significantly more than these 14 components in their mixture samples, we do not assume that our component set represents the complete molecular makeup of PB-O.…”
Section: Resultsmentioning
confidence: 99%
“…During the roasting process, lipid oxidations with various biochemical reactions occur (Chung et al, 2002;Liu et al, 2011) aside from the Maillard reactions. Peanut is an oil plant with a lipid content of about 50% (Özcan, 2010).…”
Section: Discussionmentioning
confidence: 99%